Implementasi Pendekatan Saintifik-DiscoveryLearning dalam Pembelajaran Struktur Teks Eksposisi Siswa Kelas X MM1 SMKN 8 Surabaya - Agung Pranoto; Siti Aminah (sarasvati, 2020)
In the Indonesian language curriculum that is used in the X MM Vocational School there is one of the basic competencies related to analyzing the structure and language of the exposition text. To understand the material to students, in the implementation of learning using a scientific-discovery learning approach. Based on the implementation of the scientific-discovery learning approach in learning the exposition text structure of class X MM1 students of SMKN 8 Surabaya, it can be concluded as follows. The application of the scientific approach to discovery learning model learning in exposition structure learning materials in class X MM1 students of SMKN 8 Surabaya shows the activities of students who are very good, very enthusiastic, and have the ability to think critically as expected in a constructivist learning paradigm. The level of mastery learning of students is 94.28% of students who achieve mastery individually.